Comparison of the Modified Jones Tube Technique and the DMEK EndoGlide Technique With and Without Viscoelastic Material for DMEK Tissue Preparation. Issue 2 (21st February 2023) - Christopher, Karen L.; Terrin, Staci; Lohmeier, John; Hartman, Matthew; Davidson, Richard S.; Taravella, Michael J.
Abstract : Purpose: The aim of this study was to compare endothelial cell loss for DMEK (Descemet membrane endothelial keratoplasty) tissue preparation techniques using the modified Jones tube and the DMEK EndoGlide with and without viscoelastic material to protect the endothelium. Methods: This ex vivo study included 10 DMEK grafts prepared using each of the 3 abovementioned techniques. After tissue preparation, transport conditions were simulated for a minimum of 45 hours before deployment of the DMEK tissue and quantification of endothelial cell loss. Comparisons between preparation technique groups were made using the Wilcoxon rank-sum test. Results: The Jones tube group had a mean endothelial cell loss of 11.0 ± 4.8% compared with the EndoGlide group with 12.9 ± 6.7% and the EndoGlide with viscoelastic group with 25.7 ± 15.0%. The differences between the EndoGlide with viscoelastic group and the other 2 were statistically significant both before ( P < 0.01 and P = 0.01) and after ( P = 0.01 and P = 0.02) adjusting for baseline characteristics. The difference between the EndoGlide and Jones tube groups was not significant ( P = 0.73 and P = 0.53 after adjustment). Microscopy revealed endothelial cell loss in the area of viscoelastic use for the EndoGlide with viscoelastic group. Conclusions: Both the Jones tube and DMEK EndoGlide resulted in similar low rates of endothelial cell loss after tissue preparation, transport, and deployment. However, use of viscoelastic material to protect the endothelium using the DMEK technique actually resulted in increased cell loss in the area of its application resulting in overall higher rates of cell loss across the DMEK tissue.